Three essays on the economics of crime (2024)
I present three essays on the economics of crime. In the first chapter, I study how a wealth’s negative economic shock affects crime. I collected criminal records and administrative records of more than 160,000 investors affected by the closure of a Colombian informal financial institution in 2008. I employed a regression discontinuity design, exploiting the serendipitous timing of deposit expiration dates relative to the institution’s shutdown to dissect the shock’s effects at an individual level. The results reveal an increase of 0.5% in total criminal records, 0.26% in property crimes, and 0.17% in violent crimes. However, individuals with pre-existing deposits experienced a diminished effect, with a decrease of 0.2%, resulting in a net increase of 0.3% in crime. In the second chapter (with Michael Weintraub and Leonardo Bonilla) we evaluate the impact of motorcycle restrictions in Colombia. To identify causal effects on crime, we estimate difference-in-differences models that exploit spatial and temporal variation in implementing these measures using georeferenced crime data. In four cases we find no crime reduction effects of these policies. Even when we do identify such effects, they tend to be associated with spatial displacement of crime of equal magnitude, or the results are not robust to different model specifications. Given the high costs of ensuring compliance with these measures and the costs they impose on ordinary citizens, local authorities should seek out other alternatives to improve citizen security. In the third chapter (with María del Pilar Lopez and Juan Carlos Muñoz) we examines the role of land tenure on illicit economies in the context of low institutional capacity. We focus on a property rights formalization program implemented in regions with high exposure to illicit crops in Colombia. We use administrative records of land titled by the program and high-resolution satellite imagery to identify changes in the area under coca cultivation at the level of one-square-kilometer grids in areas exposed to the program. Using an event study model, we found that in grids with at least one titled land, the reduction in the planted area with illicit crops is immediate but does not last over time. Although survey data show increased request and approval credits, we did not find a consistent effect on long-term investment and economic activity in areas exposed to the program. In this sense, we test the effect of the interaction of tenure land and market access on illicit crop reduction. Results show that grids with land tenure and road infrastructure provision reduce illicit crops between 16.2% and 22.6%.